Analysis and Numerics for Conservation Laws - Warnecke, Gerald (SpringerLink Bücher, 2005)
Wave Processes at Interfaces -- Numerics for Magnetoplasmadynamic Propulsion -- Hexagonal Kinetic Models and the Numerical Simulation of Kinetic Boundary Layers -- High-resolution Simulation of Detonations with Detailed Chemistry -- Numerical Linear Stability Analysis for Compressible Fluids -- Simulation of Solar Radiative Magneto-Convection -- Riemann Problem for the Euler Equation with Non-Convex Equation of State including Phase Transitions -- Radiation Magnetohydrodynamics: Analysis for Model Problems and Efficient 3d-Simulations for the Full System -- Kinetic Schemes for Selected Initial and Boundary Value Problems -- A Local Level-Set Method under Involvement of Topological Aspects -- Hyperbolic Systems and Transport Equations in Mathematical Biology -- Travelling Waves in Systems of Hyperbolic Balance Laws -- The Role of the Jacobian in the Adaptive Discontinuous Galerkin Method for the Compressible Euler Equations -- The Multi-Scale Dust Formation in Substellar Atmospheres -- Meshless Methods for Conservation Laws -- Simulations of Turbulent Thermonuclear Burning in Type Ia Supernovae -- Hyperbolic GLM Scheme for Elliptic Constraints in Computational Electromagnetics and MHD -- Flexible Flame Structure Modelling in a Flame Front Tracking Scheme -- Riemann-Solver Free Schemes -- Relaxation Dynamics, Scaling Limits and Convergence of Relaxation Schemes -- Multidimensional Adaptive Staggered Grids -- On Hyperbolic Relaxation Problems.